Specifics of motivation of volunteers participating in in a clinical trial of the COVID-19 vaccine - Belousova, Y. D.; Rafalsky, V. V.; Kislova, E. D. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2023)
Background. The pandemic coronavirus infection has contributed to the development of effective preventive methods to slow the spread of the virus. Mass vaccination is the only way to protect oneself from infection. The development of drugs, including vaccines, involves clinical trials (CT). The problem of conducting a CT is recruiting the necessary number of volunteers. Goal: to identify specifics of motivation of patients participating in the clinical trial of COVID-19 vaccines, as it is a very important medical and sociological issue requiring more detailed study. Materials and Methods. The results of an anonymous questionnaire survey of volunteers participating in the “EpiVacCorona” vaccine CT are presented. Overall, 203 questionnaires were analyzed, containing 19 questions answered by the residents of Kaliningrad, aged 20 to 84 years. At the stage of completion of participation in the clinical trial, information was obtained about the respondent’s attitudes to the trial, the main factors of motivation or demotivation to participate, the degree of their trust in the trial. Results. Information disseminated through the employer was an effective way to organize patient recruitment for the vaccine CT; the effectiveness of using the media was quite low. The positives of participation in the CT for volunteers were ethical considerations. Negatives for participants were the risks associated with adverse reactions or receiving a placebo. Relatives had the greatest influence on the volunteers’ decision to participate in the CT, and medical professionals, media personalities, and scientists had less influence. Conclusion. The results will help to improve patient recruitment, patient awareness of the CT, and the benefits to medicine and society. Motivating and demotivating factors will improve patient recruitment.